Discussion of Disciplinary Literacy in the Science Classroom (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2020)
Disciplinary Literacy in the science classroom is often overlooked as part of a science curriculum.  Instead, teachers focus on content area reading which is a generalized approach applied across all disciplines.  This manuscript explores what disciplinary literacy is and provides a comparison to content area reading.  It examines a supporting theory of disciplinary literacy and discusses science’s distinction as a unique discipline.  In addition, current implementations and recommendations for classroom utilization of the technique are addressed. We, as science educators, need to recognize the essentiality of science disciplinary literacy to appreciate why our profession may need guidelines regarding how to implement this method for the benefit of our students.
Keywords: Disciplinary Literacy; Science; Content Area Reading; Discourse Theory